The Ultrasound Challenge 2.0: Introducing Interinstitutional Competition in Medical Student Ultrasound Education. (1st December 2014) - Cortez, Eric J.; Boulger, Creagh T.; Eastin, Travis; Adkins, Eric J.; Granitto, Emily; Pollard, Katherine; Bahner, David P.
Abstract : The Ultrasound Challenge was developed at The Ohio State University College of Medicine to introduce focused ultrasound to medical students. The goal was to develop experience in ultrasound through practice and competition. Initially this competition was held between Ohio State University College of Medicine students from years 1 through 4. The Ultrasound Challenge 2.0 was held in 2013. The event expanded on the previous structure by including students from the Wayne State University College of Medicine. The goal of this article is to describe our experiences with expansion of our interinstitutional ultrasound event. The challenge consisted of 6 stations: focused assessment with sonography for trauma, aortic ultrasound, cardiac ultrasound, pelvic ultrasound, musculoskeletal ultrasound, and vascular access. The participants were given a handbook outlining the expectations for each station ahead of time. Vascular access was graded in real time using the Brightness Mode Quality Ultrasound Imaging Examination Technique (B‐QUIET) method. The remainder were timed, saved, and graded after the event by 3 independent faculty members using the B‐QUIET method. The highest score with the fastest time was the winner. The Ultrasound Challenge 2.0 included 40 participants: 31 from The Ohio State University College of Medicine and 9 from the Wayne State University College of Medicine. The makeup of the winners in all categories consisted of 1 first‐year medical student, 7 second‐year medical students, 3 third‐year medical students, and 10 fourth‐year medical students. The Ultrasound Challenge 2.0 was a success for those who participated. It provided the first known interinstitutional medical student ultrasound competition. Students from both institutions were able to practice their image acquisition skills, demonstrate abilities in a competitive environment, and develop collegiality and teamwork.